2013
DOI: 10.1007/s10482-013-0007-1
|View full text |Cite
|
Sign up to set email alerts
|

From genome mining to phenotypic microarrays: Planctomycetes as source for novel bioactive molecules

Abstract: Most members of the phylum Planctomycetes share many unusual traits that are unique for bacteria, since they divide independent of FtsZ through asymmetric budding, possess a complex life cycle and comprise a compartmentalized cell plan. Besides their complex cell biological features Planctomycetes are environmentally important and play major roles in global matter fluxes. Such features have been successfully employed in biotechnological applications such as the anaerobic oxidation of ammonium in wastewater tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
116
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(125 citation statements)
references
References 81 publications
7
116
0
1
Order By: Relevance
“…Recently, a comprehensive metabolic screen of P. limnophilus suggested that the organism is specialized to degrade plant-derived sugars and polysaccharides (62). Our results confirmed these observations and further implicated the involvement of the BMC in degrading some of these compounds.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Recently, a comprehensive metabolic screen of P. limnophilus suggested that the organism is specialized to degrade plant-derived sugars and polysaccharides (62). Our results confirmed these observations and further implicated the involvement of the BMC in degrading some of these compounds.…”
Section: Discussionsupporting
confidence: 87%
“…The propanediol is produced as a result of cofactor recycling and may be excreted; there is no obvious evidence of P. limnophilus being able to metabolize this compound (see Fig. S5 in the supplemental material, PM1 well D4), an observation corroborated by other investigators (62). Due to the PV BMC metabolism being aerobic, the end products of the BMC metabolism (DHAP and/or pyruvate) likely enter the tricarboxylic acid (TCA) cycle and generate ATP through oxidative phosphorylation.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…These authors also verified in R. baltica SH1 T sulphatase expression profiles in cells grown on different sulfated polysaccharides. Polysaccharide utilization was also confirmed by the work of Jeske et al (2013) where R. baltica was checked for potential utilization of several polymers. It was able to utilize laminarin, mannitol, pectin, chondroitin sulfate, N-acetylgalactosamine, and D-glucuronic acid.…”
Section: Interactions Between Macroalgae and Planctomycetesmentioning
confidence: 60%
“…This process is also critical to operation of the global nitrogen cycle, producing much of the nitrogen in the air we breathe via anaerobic ammonium recycling in environments such as the ocean's oxygen minimum zones (Kalvelage et al 2011). As a unique divergent unexplored group of bacteria, planctomycetes are an emerging source of novel secondary metabolites, which very well might be useful for drug development (Jeske et al 2013 The first meeting dedicated to these bacteria took place in early March 2013 at the Heidelberg University, thanks to a generous donation from the EMBO Courses and Workshops program (http://www.embo. org/funding-awards/courses-workshops).…”
Section: Health-and Industrial Implicationsmentioning
confidence: 99%